Design of automatic fire extinguishing system with interactive web display - Adziimaa, Ahmad Fauzan; Azizah, Salma (Jurnal Nasional Aplikasi Mekatronika, Otomasi dan Robot Industri (AMORI), 2024)
An automatic fire extinguishing system prototype has been designed. This design consists of software and hardware design. Software design involves sensors, actuators, controllers, sim900 modules and website interfaces. Hardware design is to make a prototype fire extinguishing system. Fire extinguishing system testing is done by testing the system's components such as sensors, actuators, sim900 modules, and website responses to the database. LM35 Sensor testing resulted in a measurement error of 3.29% with a measurement accuracy of 96.8% and MQ135 Sensor testing resulted in an error of 16.6% with a measurement accuracy of 90.4%. The MQ135 Sensor error is quite large because the standard measuring instrument used as a comparison measures changes in ppm levels very quickly. The actuator test results show that the buzzer can provide notification when the LM35 Sensor exceeds the set point of 57 ℃ and the MQ135 Sensor reaches 101 ppm. The relay is active when both sensors have reached the set point, and the pump will turn on to extinguish the fire. The results of testing the entire system show that the sensor works well in detecting temperature and smoke level changes so that the actuator will turn on when the temperature and smoke levels have reached the set point. The SIM900 module will send an SMS to the user if a fire is indicated. The interface of this system displays the temperature measurement levels and smoke levels in real time on the website.